PWE-033 The Incidence and Cost of Unexpected Hospital Attendance Following Elective Outpatient Flexible Sigmoidoscopy. (4th June 2013) - Gordon, H; Brindley, J H; Zheng, C; Graby, J; Abdullah, M A; Mawdsley, J; Beveridge, I; Monahan, K
Abstract : Introduction: Outpatient flexible sigmoidoscopy is an increasingly utilised investigation shown to be effective in the detection and prevention of bowel cancer. The procedure is thought to entail a low risk of complications. However, recent literature suggests the complication rate of other endoscopic procedures may be up to 10 fold that traditionally quoted (1). The true complication rate of flexible sigmoidoscopy is of particular importance as the UK is introducing the Bowel Cancer Screening Programme (BCSP) by which all citizens will be offered the procedure at age 55. Methods: The aim of this study was to identify the morbidity and related healthcare costs of unexpected hospital attendance following outpatient flexible sigmoidoscopy. An observational study of A&E attendances and admissions occurring within 14 days of all outpatient flexible sigmoidoscopies which took place in 2011 was conducted. All procedures took place at West Middlesex University Hospital, London. Data was collected using the hospital's electronic records system, enterpriseCAMIS®. Cases were analysed to assess whether reattendance could be attributed to the procedure, and healthcare costs were determined. Results: Of the 1137 outpatient flexible sigmoidoscopies performed, 18 patients (1.58%) presented to A&E within 14 days. Only 2 of these attendances were thought to be related to the procedure (0.18%). 1 case resulted in a 5 day admission due to bleeding post polypectomy. The second A&E attendance was also due to bleeding. The cost of the above admission was £4, 682. Including the related A&E attendance, the total financial burden of related reattendance following flexible sigmoidoscopy was approximately £4, 827 in 2011. This equates to an additional cost of £4.25 per procedure. Cost of hospital attendance within 14 days of outpatient flexible sigmoidoscopy (WMUH 2011, n = 1137): Conclusion: This study suggests outpatient sigmoidoscopy is relatively safe, with complications necessitating reattendance occurring following 0.18% procedures. The financial burden of hospital reattendance within our UK based study population was minimal, supporting the cost effectiveness of extending services for National bowel cancer screening programmes. Disclosure of Interest: None Declared. Reference: Leffler D A, Kheraj R, MD; Garud S, Neeman N, Larry A, Nathanson A, Kelly C P, Sawhney M, Landon B, Doyle R, Rosenberg S, Aronson M; The Incidence and Cost of Unexpected Hospital Use After Scheduled Outpatient Endoscopy, Arch Intern Med . 2010 Oct 25; 170(19):1752–7